Pola Komunikasi Tari Rejang Pala di Desa Adat Nongan Kecamatan Rendang Kabupaten Karangasem - sukariawan, madesukariawan; Ulio, Ulio (UHN IGB Sugriwa Denpasar, 2025)
Sacred or wali dance is a dance that is performed in the context of a yadnya or a certain series of rituals. Every sacred dance has a magical religious value that is highly believed by the community. One of the Rejang Pala dances performed during the Usabha Pala ceremony at Balang Tamak Temple, Nongan Traditional Village. What's unique is that this dance disappeared for almost a century but was still able to be revived because there are good communication patterns in the rejang pala dance. The communication patterns in question are: 1) Intrapersonal Communication, namely the dancer's high sradha and devotional service which raises the vibrations of the dancer's soul; 2) Interpersonal Communication, namely two-way communication between me, srati banten and the community to announce the winner of the rejang pala coil; and 3) nonverbal communication, namely as an expression of community gratitude which is made concrete by offering the rejang pala dance.